2016
DOI: 10.14214/sf.1672
|View full text |Cite
|
Sign up to set email alerts
|

Managing boreal forests for the simultaneous production of collectable goods and timber revenues

Abstract: Highlights• We found a strong conflict between bilberry production and timber revenues, resulting in large losses of timber revenues when increasing bilberry production.• The conflicts between other collectables (cowberry, cep) and timber production were relatively small. • With careful forest planning, there is potential to simultaneously produce high levels of collectable goods and timber revenues in the landscape. AbstractTimber production is an economically important provisioning ecosystem service in fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The production of B. edulis was largely in synergy with timber production, competing only near the maximal yields (Figure 7, Article II). Similar results were found in a study regarding trade-offs at near-maximal production levels of several NWFPs (including mushrooms) and timber in Finland (Peura et al 2016;Kurttila et al 2018). These results were expected, because in the studies of Peura et al (2016) and Kurttila et al (2018), the model for B. edulis was the same or based on the same data as in this study.…”
Section: Forest Owners' Roles and Possibilities In Mushroom Marketssupporting
confidence: 90%
See 1 more Smart Citation
“…The production of B. edulis was largely in synergy with timber production, competing only near the maximal yields (Figure 7, Article II). Similar results were found in a study regarding trade-offs at near-maximal production levels of several NWFPs (including mushrooms) and timber in Finland (Peura et al 2016;Kurttila et al 2018). These results were expected, because in the studies of Peura et al (2016) and Kurttila et al (2018), the model for B. edulis was the same or based on the same data as in this study.…”
Section: Forest Owners' Roles and Possibilities In Mushroom Marketssupporting
confidence: 90%
“…Similar results were found in a study regarding trade-offs at near-maximal production levels of several NWFPs (including mushrooms) and timber in Finland (Peura et al 2016;Kurttila et al 2018). These results were expected, because in the studies of Peura et al (2016) and Kurttila et al (2018), the model for B. edulis was the same or based on the same data as in this study. In the joint production of timber and mushrooms, the forest owner can prolong the picking period by up to 7 years without remarkably affecting the total SEV (Table 4, Article II).…”
Section: Forest Owners' Roles and Possibilities In Mushroom Marketssupporting
confidence: 90%
“…We used net present income as the measure of timber production. This was calculated by multiplying the recent average prices for different timber assortments (Peltola 2014) by the quantity of each assortment harvested during thinnings and/or final felling. We used a discount rate of 3% to discount income generated in the future.…”
Section: Measurement Of Objectivesmentioning
confidence: 99%
“…These scales reflect real administrative and/or natural boundaries, with increasing numbers of forest owners included within each scale. In Finland, the majority of production forests are privately owned and forest holdings are comparatively small with an average size of approximately 30 ha (Peltola 2014). Large-scale, landscape-level forest management planning may thus require the cooperation of several forest owners and potentially compensation systems that make the plan acceptable for all of them (Kurttila et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the common practice of RFM focusing solely on timber production reduces carbon storage in boreal forests compared with optimal forest management (Triviño et al, 2016). Focusing on timber production can also be in conflict with other economically beneficial forest uses, such as recreation and harvest of non-timber forest products (e.g., berries and mushrooms) (Peura et al, 2016). Earlier research has shown that diversifying forest management is a cost-efficient tool for enhancing ecosystem services (Miina et al, 2016;Triviño et al, 2015) and biodiversity (Mönkkönen et al, 2014) in production forest landscapes.…”
Section: Introductionmentioning
confidence: 99%